Evaluation of infection prevention and control in a Moroccan university hospital using the IPCAF tool - Melalka, Lamia; Assi, Fouad; Zouhdi, Mimoun; Sekhsokh, Yassine (The Journal of Infection in Developing Countries, 2026)
Introduction: Healthcare-associated infections (HAIs) are a significant global health challenge. In Morocco, while the prevalence of HAIs has been studied in university hospitals, limited research has focused on the effectiveness of infection prevention and control (IPC) programs. This study evaluates the adherence of 8 Moroccan hospitals to IPC standards using the Infection Prevention and Control Assessment Framework (IPCAF). Methodology: Eight Moroccan hospitals participated in this study. The IPC compliance of each hospital was assessed using the IPCAF tool, which evaluates IPC committees, staff training, infrastructure, and surveillance systems. Results: The study showed significant variation in IPCAF scores. Hospitals such as Maternity and Reproductive Health Hospital - Orangers, Ibn Sina Hospital, and National Institute of Oncology achieved high compliance, with scores of 657.5 and 652.5, reflecting 82.19% and 81.56% compliance. These hospitals demonstrated strong IPC committees, effective training, and consistent surveillance. In contrast, Arrazi Hospital and Souissi Maternity had lower scores, with HAI scoring 352.5, indicating gaps in IPC practices. The lower-scoring hospitals struggled with infrastructure, staff involvement, and adherence to IPC guidelines. Conclusions: The study highlights the importance of leadership commitment, regular training, and surveillance to improve IPC outcomes. It emphasizes the need for targeted interventions in underperforming hospitals to address gaps in infrastructure and staff involvement, thereby enhancing patient safety and infection control standards in Morocco.